Development of risk management framework in Malaysian landscape project - S.Muthuveeran, Adam Aruldewan (2020)
The nature of landscape projects that is dynamic, complex, fast-tracked, and with subjective outcome exposes the projects to a high degree of risk. This project risk could potentially become a critical issue that hinders the project from achieving its objectives. Risk management widely practised to systematically manage project risk, which could adversely affect the project outcome. However, many landscape projects in Malaysia do not manage risk effectively, and no formal risk management is applied. This scenario denotes the presence of a gap in risk management practices in the landscape architecture field in Malaysia. Hence, this research aimed to explore the risk management application in Malaysian landscape project management. In achieving this aim, the research determined past project issues’ controllability, analysed the current management of project risk, and formulated a risk management application framework. This research employed qualitative research along with exploratory research purpose. Findings from the literature review synthesised to formulate a conceptual framework for the risk management application. The fieldwork data collection completed through an in-depth interview with landscape architectural expert and case study to completed landscape project review. Along, a focus group discussion employed to validate the conceptual framework. Then, the collected data were analysed using content and thematic analyses. The findings suggest that the past project issues are controllable earlier but occurred due to an ineffective practice to manage it. Project risk not managed systematically according to the suggested process whereby risk process practised incompletely, ineffectively integrated into project lifecycle and limited risk tools and techniques used. The practised impaired by an unavailable formal risk management application. Hence, the research recommends developing a conceptual framework with a specific framework integrating risk process into the project lifecycle. The framework theoretically improves the landscape architecture body of knowledge. Practically it provides a much-needed guide for Malaysia’s landscape architects in managing their project risk. This practice towards achieving the project objectives, thus enhance project performances that subsequently contribute to the country’s landscape aspiration.